Effect of Compression Pressure and Coal Binding on the Fuel Properties of Biomass Pellet - Jamal M.S.; Shahinuzzaman M.; Sujan S.M.A.; Hasan M.R.; Karim M.R.; Dar M.A.; Gul R.; Amin N.; Akhtaruzzaman M. (Pleiades journals, 2023)
Biomass; Coal; Compaction; Heating; Hydrogen bonds; Van der Waals forces; Biomass Particle; Co-pelletization; Compaction of biomass; Compression pressures; Different pressures; Fuel properties; Heating value; Pellet hardness; Pelletisation; Pellets densities; Pelletizing; Biomass; Coal; Compaction; Heating; Hydrogen Bonds; Pelleting